The Relationship of Customary Law to Society in a Bipolar Indonesia - Sabrina Dwi Lestari; Abel Yap Shun Kit (Indonesian Journal of Administrative Law and Local Government, 2024)
Indonesia has a national motto "Bhinneka Tunggal Ika", which can be interpreted as "different but still one". The motto reflects the diversity of Indonesian people including ethnicity, religion, race, intergroup (SARA), culture, and language. Since ancient times and the days of the Polynesian Malays, this diversity has existed as a result of differences in descent, place of residence, as well as the inclusion of religious and cultural influences mixed with local indigenous cultures throughout Indonesia. With diversity, the development of human life begins continuously until it creates a habit. Over time, this habit becomes a "custom" originating from the local community. The custom should apply to all members of the community as a legal identity. Therefore, "customary law" was created which is a product of the rules of human habits in social life. With customary law, we will understand more about Indonesian legal culture. The purpose of writing this article is to find out more about the relationship between customary law and the people of Indonesia, who are diverse. The research creates a result that shows that there is a bound relationship between customary law and Indonesian society.